Women in the Silent Cinema Histories of Fame and Fate - Förster, Annette (Framing Film, 2016)
This authoritative book offers comprehensive accounts of the professional journeys of three women working in silent film in the Netherlands, France, and North America. Film historian Annette Förster presents a careful assessment and exploration of the long careers of Dutch stage and film actress Adriënne Solser, French stage and screen actress and filmmaker Musidora, and Canadian-born actress and filmmaker Nell Shipman. In studying these three early pioneers, Förster renders builds a larger analysis of the interaction between the popular stage and the silent cinema, and how that interaction appeared from the perspective of women at work across both realms. A wealth of archival research provides fresh insights into Dutch stage and screen comedy, the French revue, and the American Northwest drama of the 1910s, illuminating the lives of three important women in the early era of film